Prevalence of endo and enctoparasites in psittaciformes raised in the state of Espirito Santo (Veterinária Notícias, 2021)
Birds are parasitized by many parasites, and at wildlife animals are less vulnerable to the changes caused by parasitism, nevertheless in captivity their vulnerability may increase by different factors, including precarious hygiene and management. Birds of the order Psittaciformes frequently live together with people, and it may causes health and environment threats. Then, the objective of the current study was to accomplish parasitological exams in captive Psittaciformes birds aiming to know their parasitological fauna, and evaluate the results with the type of management and the environment where they are, to adopt appropriate prophylaxis measures. This work was authorized by the Ethics Commission in the Use of Animals at UFES from Alegre, and by the Biodiversity Information and Authorization System (SISBIO) of ICMBio. There were analyzed 200 birds of four breedings in Espírito Santo state, being that 126 couple of cockatiels are from domestic breedings in the county of Alegre and 74 individuals of parrots from the Zoo Park da Montanha Zoo, in Marechal Floriano. The fecal samples were collected and processed by the Simple Fluctuation Centrifugal technique in parasitology lab of HOVET-UFES, and the parrots and cockatiels’ feathers were manually analized and in the stereomicroscope. The environment and heath aspects where the birds were living were analyzed. The obtained data were summarized by descriptive statistics. The parasites found were Eimeria sp., Capillaria sp., Ascaridia sp., Neopsittaconirmus sp. and Neorthydelasma sp. The prophylactic and control recommendations were made based on the results of this study and on the evaluation of the current situation that each bird was, showing an association of the appropriate management with the birds with the presence and diversity of parasites. This study emphasizes the need of more parasitological studies in birds of this order, since they are charismatic animals and live together harmoniously with the society.